RISK MITIGATION IN SUGARCANE PLANTING USING FAILURE MODE AND EFFECT ANALYSIS METHOD - Marodiyah, Inggit; Cahyana , Atikha Sidhi; Nurmalasari , Intan Rohma (Antis-Publisher, 2024)
Farming in cultivation always faces challenges, including land/land area, acquisition of superior seeds, fertilization, maintenance and labor. As a result of these uncertain risks, farmers are encouraged to always have high motivation, be creative and innovative, and dare to take risks by responding to existing opportunities. Therefore, it is necessary to make maximum efforts in providing understanding to farmers to carry out sugarcane cultivation. Problems inevitably arise because they dare to take unnecessary risks, so it requires questions in dealing with the impact, so risk mitigation is needed to reduce risk. Therefore, the purpose of this study was to determine the highest risk in the sugarcane planting process in increasing productivity. Data was collected by documentation through the distribution of questionnaires. The method used in this research is FMEA (Failure Mode Effect Analysis) based on ex ante, interactive and ex post strategies. The results of this study are Risk mitigation against the highest risk, the first is to make a good irrigation system, the second is to give pest control drugs in accordance with the provisions and the third is to pay attention to kletek time and carry out klentek properly.